Big Capital in an Unequal World : The Micropolitics of Wealth in Pakistan - Armytage, Rosita (Karachi Liberty Publishing, 2023)
Following the hidden lives of the global "1%", this book examines the networks, social practices, marriages, and machinations of the elite in Pakistan. In doing so, it reveals the daily, even mundane, ways in which elites contribute to and shape the inequality that characterizes the modern world. Operating in a rapidly developing economic environment, the experience of Pakistan's wealthiest and most powerful members contradicts widely held assumptions that economic growth is leading to increasingly impersonalized and globally standardized economic and political structures
Include References and Index
Keywords: Wealth -- Pakistan -- Rich people -- Economic history